A Study of Difficulty in English Sentence Writing of the Myanmar Students at Mahachulalornkornrajavidyalaya University - Ven. Arlawka; Kanokkamalade , Veerakarrn; Klinchan, Nilratana (วารสารจิตวิทยาพุทธศาสตร์ประยุกต์เพื่อสังคม, 2021)
This research was to study the difficulty in English sentence writing of Myanmar students at Mahachulalornkornrajavidyalaya University.Population was 253, the sample participants of this study were 153 B.A and M.A Myanmar students who were studying at the Faculty of Humanities in MCU. As a descriptive research, a research questionnaire with 16 questions including general information of the students was applied for quantitative data collection and the responses of students were analyzed the difficulties in English sentence writing of the students. For qualitative data collection, the researcher had done an In-depth interview to fifteen suitable Myanmar students; the responses of the students were recorded by voice recorder.The result of the study to analyze the collective data, the finding results occurred that half of Myanmar students had difficulty in English sentence writing. So, the result of average was moderate level equal to mean = 3.09, (S.D. 1.380) in the statements of difficulties in English sentence writing. In the result of providing way, the result of average level was high equal to mean =3.91, (S.D. 1.189) because majority of the students were willing for providing way to write English sentences. The main results of in- depth interview was that the Myanmar students had difficulties in English sentence writing because the students were weak in four kinds of English sentences, phrases, clauses, using comma and using conjunction. Furthermore, the students could not analyze English sentences in reading books. Therefore, it can be concluded that half of Myanmar students have difficulties in English sentence writing and majority of the students are willing for providing way to write English sentences professionally.